An overlooked EDI issue… can valuing the diversity of third space professionals support a more sustainable future in higher education? - Emmajane Milton; Emma Yhnell; Kathryn Jones (Journal of Learning Development in Higher Education)
Do teaching-focused colleagues in the higher education (HE) sector feel they belong? Or do they often feel like misfits who challenge the status quo by not conforming to traditional academic stereotypes? In this short opinion piece, we explore the complexity and diversity of roles held by third space professionals in teaching-focused roles and the impact this has on their sense of identity, belonging, and value. We argue that there needs to be a concerted effort to grapple and genuinely engage with this thorny and deep-rooted issue, to enable these colleagues to feel they are included and valued in their institutions and across the sector.